Negative pole piece, preparation method thereof and battery
By using a high spherical first silicon material as the bottom layer and a low spherical second silicon material as the upper layer in the negative electrode sheet of the lithium-ion battery, combined with the gradient design, the performance problems caused by volume expansion of the silicon material are solved, and the high energy density and fast charging performance are achieved.
Patent Information
- Application Number
- CN202510010717.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The volume of silicon material expands too much during charging and discharging of lithium-ion batteries, resulting in material cracks, interface generation and new SEI film consumption, affecting battery performance and unable to take into account high energy density and fast charging performance.
A negative electrode sheet is designed, using a first silicon material with a high spherical morphology (S1≥0.80) as the base material, and a second silicon material with a low spherical morphology (0.30≤S2≤0.65) is used on the upper layer to optimize the compaction density and kinetic properties of the silicon material through gradient design.
The overall compaction density and energy density of the negative electrode sheet are improved, the volume expansion stress is reduced, the structural stability and dynamic performance of the material are enhanced, and the high energy density and fast charging performance are achieved.
Smart Images

Figure CN119812214A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy batteries, and in particular to a negative electrode sheet and a preparation method thereof, and a battery. Background Art
[0002] With the rapid development of science and technology, the continuous improvement of the energy density of lithium-ion batteries and the development of high-energy-density lithium-ion batteries have become an inevitable trend in the development of lithium-ion batteries. In terms of improving energy density, increasing the theoretical specific capacity of the negative electrode active material of lithium-ion batteries is one of the most effective ways. The theoretical specific capacity of silicon materials at room temperature is as high as 3579mAh / g, which is more than 10 times the theoretical specific capacity of graphite negative electrodes of commercial lithium-ion batteries today. In a short period of time, it is considered to be the most promising negative electrode material for commercial application to improve the energy density of lithium-ion batteries. However, the volume change of silicon materials during the charging and discharging process is as high as 300%. The huge volume expansion will cause cracks in silicon particles, generate new interfaces, and lead to the formation of new SEI films to consume electrolytes, affecting the performance of the battery. In addition, under this expansion, the conductive network of the negative electrode is easily destroyed, some particles lose electrical contact, the battery capacity decays faster, and the kinetic performance is lost. Therefore, how to inhibit the volume expansion of silicon materials during the charging and discharging process and improve the stability and kinetic performance of silicon-containing negative electrode sheets is an urgent problem to be solved in the application of silicon materials in the negative electrode of lithium-ion batteries. Summary of the invention
[0003] In view of this, the present invention is committed to providing a negative electrode plate and a preparation method thereof and a battery, so as to solve the problem in the prior art that the silicon negative electrode material has excessive volume expansion and insufficient kinetic performance during actual use, resulting in the inability to have both high energy density and fast charging performance.
[0004] In order to solve the above technical problems, this application is implemented as follows:
[0005] A first aspect of the present invention provides a negative electrode plate, the negative electrode plate comprising a current collector, a first negative electrode active material layer disposed on a surface of the current collector, and a second negative electrode active material layer disposed on a surface of the first negative electrode active material layer away from the current collector;
[0006] The first negative electrode active material layer includes a first silicon material, and the second negative electrode active material layer includes a second silicon material;
[0007] Wherein, the sphericity S of the first silicon material 1 ≥0.80; the sphericity S of the second silicon material 2 In the range of 0.30 to 0.65;
[0008] The first silicon material and the second silicon material satisfy the following relationship: 1 ≥M2 , where M 1 represents the mass percentage of the first silicon material in the first negative electrode active material layer, M 2 represents the mass percentage of the second silicon material in the second negative electrode active material layer.
[0009] Optionally, the sphericity S of the first silicon material is 1 In the range of 0.80 to 0.95; the sphericity S of the second silicon material 2 In the range of 0.40 to 0.60.
[0010] Optionally, the first silicon material and the second silicon material satisfy the following relationship: 1%≤M 1 -M 2 ≤5%.
[0011] Optionally, the mass percentage M of the first silicon material in the first negative electrode active material layer is 1 The range is 5%≤M 1 ≤30%; and / or, the mass percentage of the second silicon material in the second negative electrode active material layer is M 2 The range is 0<M 2 ≤25%.
[0012] Optionally, a mass ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:0.42-2.34.
[0013] Optionally, the first silicon material and the second silicon material are independently selected from SiO x (0<x<2), at least one of pre-lithiation silicon oxide, pre-magnesiation silicon oxide, silicon alloy, sand-ground silicon carbon and vapor deposited silicon carbon; the 5T powder compaction density of the first silicon material is 1.11~1.25g / cc; the 5T powder compaction density of the second silicon material is 1.00~1.10g / cc.
[0014] Optionally, the first negative electrode active material layer also includes a first active material, and the second negative electrode active material layer also includes a second active material; optionally, the first active material is a first graphite material, and the second active material is a second graphite material; optionally, the first graphite material and the second graphite material are each independently selected from at least one of artificial graphite, natural graphite and mesophase carbon microbeads.
[0015] A second aspect of the present invention provides a method for preparing the above-mentioned negative electrode sheet, the preparation method comprising the following steps:
[0016] S1, preparing a first negative electrode active material layer slurry containing a first silicon material; applying the first negative electrode active material layer slurry to the surface of a current collector and performing a first drying treatment to obtain a current collector having a first negative electrode active material layer disposed on the surface;
[0017] S2. Prepare a second negative electrode active material layer slurry containing a second silicon material, apply the second negative electrode active material layer slurry on the surface of the first negative electrode active material layer, and perform a second drying process.
[0018] Optionally, the first negative electrode active material layer slurry also contains a first active material, a first conductive agent, a first binder, a first thickener and a first negative electrode solvent; the second negative electrode active material layer slurry also contains a second active material, a second conductive agent, a second binder, a second thickener and a second negative electrode solvent; the first conductive agent and the second conductive agent are each independently selected from at least one of conductive carbon black, graphene and carbon nanotubes; the first binder and the second binder are each independently selected from at least one of styrene-butadiene rubber, polyacrylic acid, polyvinyl pyrrolidone, polyaniline, polyimide, polysiloxane, polystyrene-butadiene rubber, epoxy resin, polyester resin and polyurethane resin; the first thickener and the second thickener are each independently selected from sodium carboxymethyl cellulose and / or lithium carboxymethyl cellulose; the first negative electrode solvent is water; the second negative electrode solvent is water.
[0019] A third aspect of the present invention provides a battery, the battery comprising a negative electrode plate, the negative electrode plate comprising the above-mentioned negative electrode plate and / or the negative electrode plate prepared according to the above-mentioned preparation method.
[0020] Through the above technical solution, the beneficial technical effects of the present invention are:
[0021] (1) The first negative electrode active material layer in the negative electrode plate of the present invention uses a first silicon material with a relatively high sphericity (S1≥0.80). The spherical structure design of this silicon material has strong compressive strength and high compaction density. When placed at the bottom of the plate, it can improve the overall compaction density of the negative electrode plate and improve the energy density. The silicon material has a high sphericity and is placed at the bottom, so that the contact angle with the current collector is large, which prevents the silicon material from being embedded in the current collector under high pressure rolling and causing the current collector to break. The particles with high sphericity have more uniform volume expansion stress during lithium extraction and expansion, and the overall expansion rate of the material is low, which also effectively reduces the problem of current collector breakage caused by silicon expansion during the cycle. The second negative electrode active material layer uses a second silicon material with a relatively low sphericity (0.30≤S 2≤0.65), this silicon material has low sphericity and more surface active sites, which is conducive to the rapid transmission and diffusion of lithium ions; and the low sphericity and low compaction density of the material, when placed on the upper layer of the electrode and mixed with graphite, it is conducive to creating more pores, which is conducive to the rapid transmission of electrolyte and lithium ions, and improves the overall dynamic performance of the electrode.
[0022] (2) Silicon content M of the first negative electrode active material layer of the present invention 1 and the silicon content M of the second negative electrode active material layer 2 A gradient design is adopted, wherein the content of the first silicon material and the content of the second silicon material satisfy the following relationship: 1 ≥M 2 . The silicon material of the first negative electrode active material layer has a high compaction density and high structural strength. The content is high in the bottom layer of the electrode, which is beneficial to improving the overall energy density of the negative electrode. The silicon material of the second negative electrode active material layer has a low compaction density. A small amount of addition can effectively improve the dynamic performance of the upper layer of the negative electrode, while avoiding the huge volume expansion and contraction of the silicon material during the cycle, which causes a large amount of silicon material to float to the surface of the active material layer, and silicon particles piercing the diaphragm to cause safety problems. This gradient design makes the compaction density of the upper and lower layers of the electrode closer, avoiding the peeling of the material layer caused by the large compaction density difference between the upper and lower layers.
[0023] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.
[0025] Figure 1 Shown is a schematic diagram of the negative electrode sheet of the present invention.
[0026] Description of Reference Numerals
[0027] 1. Current collector
[0028] 2. First negative electrode active material layer
[0029] 3. Second negative electrode active material layer
[0030] 4. First Silicon Materials
[0031] 5. Second Silicon Material
[0032] 6. First active material
[0033] 7. Second active material DETAILED DESCRIPTION
[0034] The present invention discloses a negative electrode plate and a method for preparing the same and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0035] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0036] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0037] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0038] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0039] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0040] In order to solve the problem that the silicon material in the prior art has excessive volume expansion and insufficient dynamic performance during actual use, resulting in the inability to have both high energy density and fast charging performance, the present invention adopts the following technical solution:
[0041] A first aspect of the present invention provides a negative electrode plate, such as Figure 1 As shown, the negative electrode plate includes a current collector, a first negative electrode active material layer disposed on the surface of the current collector, and a second negative electrode active material layer disposed on a surface of the first negative electrode active material layer away from the current collector;
[0042] The first negative electrode active material layer includes a first silicon material, and the second negative electrode active material layer includes a second silicon material;
[0043] Wherein, the sphericity S of the first silicon material 1 ≥0.80; the sphericity S of the second silicon material 2 In the range of 0.30 to 0.65;
[0044] The first silicon material and the second silicon material satisfy the following relationship: 1 ≥M 2 , where M 1 represents the mass percentage of the first silicon material in the first negative electrode active material layer, M 2 represents the mass percentage of the second silicon material in the second negative electrode active material layer.
[0045] The negative electrode plate in the present invention includes a first negative electrode active material layer and a second negative electrode active material layer, wherein the silicon material contained in the first negative electrode active material layer has a high sphericity, which is beneficial to improving the overall structural stability of the negative electrode plate and improving the cycle performance and expansion performance of the battery cell; the silicon material contained in the second negative electrode active material layer has a sphericity in the range of 0.30 to 0.65, which helps to control the side reaction between the silicon material and the electrolyte while ensuring the energy density of the battery cell, and improve the cycle and fast charging performance of the battery cell. At the same time, the content of the first silicon material and the content of the second silicon material in the present invention satisfy the following relationship: M 1 ≥M 2 , which can make the compaction density of the upper and lower layers of the pole piece closer, and avoid the material layer peeling caused by the large compaction density difference between the upper and lower layers.
[0046] The term "sphericity" involved in the present invention is used to characterize the parameters of particle morphology. The closer the particle is to a sphere in morphology, the closer its sphericity is to 1. In the present invention, the sphericity is directly measured by a device, for example, using a Morphologi-4 fully automatic particle size and shape analyzer (purchased from Malvern Panalytical, UK) for measurement, and the test method can be dry dispersion and / or static image method.
[0047] In an exemplary embodiment of the present invention, the sphericity S of the first silicon material is 1 In the range of 0.80 to 0.95; the sphericity S of the second silicon material 2In the range of 0.40 to 0.60. In this embodiment, the fast charging performance of the battery cell is less affected, the structural stability of the silicon material is improved, the overall structural stability of the negative electrode plate is improved, and the cycle performance and expansion performance of the battery cell are improved.
[0048] According to the present invention, the percentage content M of the first silicon material in the first negative electrode active material layer is 1 and the percentage content M of the second silicon material in the second negative electrode active material layer 2 The gradient difference M 1 -M 2 If M is controlled within a reasonable range, the obtained silicon negative electrode sheet and the battery cell containing the negative electrode sheet have relatively balanced energy density, fast charging performance, cycle performance and expansion performance. 1 -M 2 The difference is too small. At this time, the content of the second silicon material in the second negative electrode active material layer is relatively high. Due to the low compaction density of the second silicon material, the pole piece cannot be rolled to the target compaction density, and the energy density of the battery cell decreases instead of increases. In addition, the content of the second silicon negative electrode material increases, resulting in deterioration of the fast charging performance, cycle performance and expansion performance of the battery cell. At the same time, due to the mismatch in the volume expansion of the upper and lower pole pieces, the pole piece is demolded. If the difference between M1 and M2 is too large, the content of the second silicon material in the second negative electrode active material layer decreases, resulting in a decrease in the energy density of the battery cell. In addition, the low silicon content leads to a decrease in lithium insertion active sites and a decrease in the created pore space, resulting in deterioration of the fast charging performance, but improved cycling and expansion performance. Exemplarily, the first silicon material and the second silicon material may satisfy the following relationship: 1%≤M 1 -M 2 ≤5%.
[0049] In an exemplary embodiment of the present invention, the mass percentage M of the first silicon material in the first negative electrode active material layer is 1 The range can be 5%≤M 1 ≤30%; and / or, the mass percentage of the second silicon material in the second negative electrode active material layer is M 2 The range can be 0<M 2 ≤25%.
[0050] According to the present invention, a reasonable mass ratio of the first negative electrode active material layer and the second negative electrode active material layer can make the silicon negative electrode plate and the battery cell containing the negative electrode plate have a relatively balanced energy density, fast charging performance, cycle performance and expansion performance. If the proportion of the first negative electrode active material layer is too small, that is, the lower layer active material that provides high compaction is reduced, the plate cannot be rolled to the target compaction density, the thickness of the plate increases, the energy density of the battery cell decreases, the fast charging performance deteriorates, and the proportion of the second silicon material of the entire plate increases, resulting in an increase in side reactions with the electrolyte, and the cycle performance and battery cell expansion deteriorate; if the proportion of the first negative electrode active material layer is too large, the overall silicon content of the plate increases, the energy density of the battery cell increases, but the overall proportion of the second silicon material of the plate decreases, the fast charging performance deteriorates, and a slight lithium precipitation phenomenon occurs. In the present invention, the mass ratio of the first negative electrode active material layer and the second negative electrode active material layer can be 1: 0.42~2.34. Illustratively, the mass ratio of the first negative electrode active material layer to the second negative electrode active material layer can be any value among 1:0.42, 1:0.5, 1:0.75, 1:1, 1:1.25, 1:1.5, 1:1.75, 1:2, 1:2.25 and 1:2.34, or any value within the range consisting of any two of the above values.
[0051] According to the present invention, the compaction density of the 5T powder of the first silicon negative electrode may be 1.11 to 1.25 g / cc; the compaction density of the 5T powder of the second silicon negative electrode may be 1.00 to 1.10 g / cc.
[0052] Exemplarily, the first silicon material and the second silicon material can be independently selected from SiO x (0<x<2), at least one of pre-lithiation silicon oxide, pre-magnesiation silicon oxide, silicon alloy, sand-ground silicon carbon and vapor-deposited silicon carbon.
[0053] According to the present invention, the first negative electrode active material layer may further include a first active material, and the second negative electrode active material layer may further include a second active material; optionally, the first active material is a first graphite material, and the second active material is a second graphite material; optionally, the first graphite material and the second graphite material are each independently selected from at least one of artificial graphite, natural graphite and mesophase carbon microbeads.
[0054] A second aspect of the present invention provides a method for preparing the above-mentioned negative electrode sheet, the preparation method comprising the following steps:
[0055] S1, preparing a first negative electrode active material layer slurry containing a first silicon material; applying the first negative electrode active material layer slurry to the surface of a current collector and performing a first drying treatment to obtain a current collector having a first negative electrode active material layer disposed on the surface;
[0056] S2. Prepare a second negative electrode active material layer slurry containing a second silicon material, apply the second negative electrode active material layer slurry on the surface of the first negative electrode active material layer, and perform a second drying process.
[0057] The preparation method of the negative electrode pole piece of the present invention has a simple process and low cost. It only requires controlling the sphericity and addition amount of the silicon material added to the upper and lower layers during the negative electrode slurry preparation process. The negative electrode pole piece obtained by this preparation method is applied to the battery cell, which can significantly improve the dynamic performance, long cycle performance and energy density of the battery cell.
[0058] According to the present invention, the first negative electrode active material layer slurry may also contain a first active material, a first conductive agent, a first binder, a first thickener and a first negative electrode solvent; the second negative electrode active material layer slurry may also contain a second active material, a second conductive agent, a second binder, a second thickener and a second negative electrode solvent; the first conductive agent and the second conductive agent may be independently selected from at least one of conductive carbon black, graphene and carbon nanotubes; the first binder and the second binder may be independently selected from at least one of styrene-butadiene rubber, polyacrylic acid, polyvinyl pyrrolidone, polyaniline, polyimide, polysiloxane, polystyrene-butadiene rubber, epoxy resin, polyester resin and polyurethane resin; the first thickener and the second thickener may be independently selected from sodium carboxymethyl cellulose and / or lithium carboxymethyl cellulose; the first negative electrode solvent may be water; the second negative electrode solvent may be water.
[0059] In the present invention, the mixing ratio of each component in the first negative electrode active material layer slurry and the second negative electrode active material layer slurry can be various mixing ratios commonly used in the art, and no further limitation is made here.
[0060] A third aspect of the present invention provides a battery, the battery comprising a negative electrode plate, the negative electrode plate comprising the above-mentioned negative electrode plate and / or the negative electrode plate prepared according to the above-mentioned preparation method.
[0061] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources. The current collector used in the examples and comparative examples is copper foil.
[0062] Example 1
[0063] (1) Mixing a first silicon material, a first graphite material, a first conductive agent, a first binder and a first thickener in water to obtain a first negative electrode active material layer slurry; applying the first negative electrode active material layer slurry on the surface of a current collector and performing a first drying treatment to obtain a current collector having a first negative electrode active material layer disposed on the surface. The first silicon material is vapor-deposited silicon carbon with a sphericity S 1 The compacted density PD is 0.82. 1is 1.15 g / cc, and the mass percentage of the first silicon material in the first negative electrode active material layer is M 1 The first graphite material is artificial graphite, the first conductive agent is single-walled carbon nanotubes, the first binder is polyacrylate lithium (PAA-Li), the first thickener is carboxymethyl cellulose lithium (CMC-Li), and the mass ratio of the first silicon material, the first graphite material, the first conductive agent, the first binder and the first thickener is 9.67%: 87.03%: 0.1%: 2.8%: 0.4%.
[0064] (2) Mix the second silicon material, the first graphite material, the second conductive agent, the second binder and the second thickener in water to obtain a second negative electrode active material layer slurry, apply the second negative electrode active material layer slurry on the surface of the first negative electrode active material layer and perform a second drying process to obtain the negative electrode sheet of this embodiment. The second silicon material is vapor-deposited silicon carbon with a sphericity S 2 is 0.45, compaction density PD 2 is 1.05 g / cc, and the mass percentage of the second silicon material in the second negative electrode active material layer is M 2 The second graphite material is artificial graphite, the second conductive agent is single-walled carbon nanotubes, the second binder is PAA-Li, the second thickener is CMC-Li, and the mass ratio of the second silicon material, the second graphite material, the second conductive agent, the second binder, and the second thickener is 6.769%: 89.931%: 0.1%: 2.8%: 0.4%.
[0065] In the negative electrode sheet of this embodiment, the mass ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:1.
[0066] Example 2
[0067] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that the sphericity S of the second silicon material is 2 is 0.30, compaction density PD 2 It is 1.03g / cc.
[0068] Example 3
[0069] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that the sphericity S of the second silicon material is 2 The compacted density PD is 0.63. 2 It is 1.08g / cc.
[0070] Example 4
[0071] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that: the mass percentage M of the second silicon material in the second negative electrode active material layer is 2The mass ratio of the second silicon material, the second graphite material, the second conductive agent, the second binder and the second thickener is 4.845%:92.055%:0.1%:2.6%:0.4%.
[0072] Example 5
[0073] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that: the mass percentage M of the second silicon material in the second negative electrode active material layer is 2 The mass ratio of the second silicon material, the second graphite material, the second conductive agent, the second binder and the second thickener is 8.703%: 87.997%: 0.1%: 2.8%: 0.4%.
[0074] Example 6
[0075] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of Embodiment 1, except that the mass ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:2.34.
[0076] Example 7
[0077] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of Embodiment 1, except that the mass ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:0.42.
[0078] Example 8
[0079] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that: the mass percentage M of the first silicon material in the first negative electrode active material layer is 1 The mass ratio of the first silicon material, the first graphite material, the first conductive agent, the first binder and the first thickener is 4.845%: 92.055%: 0.1%: 2.6%: 0.4%; the mass percentage M of the second silicon material in the second negative electrode active material layer 2 The mass ratio of the second silicon material, the second graphite material, the second conductive agent, the second binder and the second thickener is 2.907%: 93.993%: 0.1%: 2.6%: 0.4%.
[0080] Example 9
[0081] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that: the mass percentage M of the first silicon material in the first negative electrode active material layer is 1 The mass ratio of the first silicon material, the first graphite material, the first conductive agent, the first binder and the first thickener is 28.86%: 67.34%: 0.2%: 3.2%: 0.4%; the mass percentage M of the second silicon material in the second negative electrode active material layer2 The mass ratio of the second silicon material, the second graphite material, the second conductive agent, the second binder and the second thickener is 72.15%: 24.05%: 0.2%: 3.2%: 0.4%.
[0082] Example 10
[0083] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that: the sphericity S of the first silicon material is 1 It is 0.93.
[0084] Embodiment 11
[0085] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that: the mass percentage M of the second silicon material in the second negative electrode active material layer is 2 The mass ratio of the second silicon material, the second graphite material, the second conductive agent, the second binder and the second thickener is 2.907%: 93.993%: 0.1%: 2.6%: 0.4%.
[0086] Example 12
[0087] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of Embodiment 1, except that the mass ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:4.
[0088] Embodiment 13
[0089] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of Embodiment 1, except that the mass ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:0.25.
[0090] Embodiment 14
[0091] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that: the mass percentage M of the first silicon material in the first negative electrode active material layer is 1 The mass ratio of the first silicon material, the first graphite material, the first conductive agent, the first binder and the first thickener is 2.907%: 93.993%: 0.1%: 2.6%: 0.4%; the mass percentage M of the second silicon material in the second negative electrode active material layer 2 The mass ratio of the second silicon material, the second graphite material, the second conductive agent, the second binder and the second thickener is 1.938%: 94.962%: 0.1%: 2.6%: 0.4%.
[0092] Embodiment 15
[0093] The preparation method of the negative electrode sheet of this embodiment is generally the same as that of embodiment 1, except that: the mass percentage M of the first silicon material in the first negative electrode active material layer is 1 The mass ratio of the first silicon material, the first graphite material, the first conductive agent, the first binder and the first thickener is 33.67%: 62.53%: 0.2%: 3.2%: 0.4%; the mass percentage M of the second silicon material in the second negative electrode active material layer 2 The mass ratio of the second silicon material, the second graphite material, the second conductive agent, the second adhesive and the second thickener is 28.86%: 67.34%: 0.2%: 3.2%: 0.4%.
[0094] Comparative Example 1
[0095] The preparation method of the negative electrode sheet of this comparative example is the same as that of Example 1, except that the sphericity S of the second silicon material is 2 is 0.25, compaction density PD 2 It is 0.97g / cc.
[0096] Comparative Example 2
[0097] The preparation method of the negative electrode sheet of this comparative example is the same as that of Example 1, except that the sphericity S of the second silicon material is 2 is 0.75, compaction density PD 2 It is 1.1g / cc.
[0098] Comparative Example 3
[0099] The preparation method of the negative electrode sheet of this comparative example is the same as that of Example 1, except that: the mass percentage M of the first silicon material in the first negative electrode active material layer is 1 The mass ratio of the first silicon material, the first graphite material, the first conductive agent, the first binder and the first thickener is 9.67%: 87.03%: 0.1%: 2.8%: 0.4%; the mass percentage M of the second silicon material in the second negative electrode active material layer is 2 The mass ratio of the second silicon material, the second graphite material, the second conductive agent, the second binder and the second thickener is 10.637%: 86.063%: 0.1%: 2.8%: 0.4%.
[0100] Comparative Example 4
[0101] The preparation method of the negative electrode sheet of this comparative example is the same as that of Example 1, except that: the sphericity S of the first silicon material is 1 is 0.75.
[0102] Comparative Example 5
[0103] The first silicon material, the second silicon material, the graphite material, the conductive agent, the binder and the thickener are mixed in water to obtain a negative electrode active material layer slurry; the negative electrode active material layer slurry is applied to the surface of the current collector and dried to obtain the negative electrode sheet of this comparative example. The first silicon material is vapor-deposited silicon carbon with a sphericity S 1 The compacted density PD is 0.82. 1 is 1.15 g / cc, and the mass percentage of the first silicon material in the negative electrode active material layer is M 1 The second silicon material is vapor-deposited silicon carbon, with a sphericity S 2 is 0.45, compaction density PD 2 is 1.05 g / cc, and the mass percentage of the second silicon material in the negative electrode active material layer is M 2 The graphite material is artificial graphite, the conductive agent is single-walled carbon nanotubes, the binder is PAA-Li, the thickener is CMC-Li, and the mass ratio of the first silicon material, the second silicon material, the graphite material, the conductive agent, the binder and the thickener is 4.845%: 3.3915%: 88.6635%: 0.1%: 2.6%: 0.4%.
[0105] Test Example 1
[0106] The negative electrode sheets, positive electrode sheets and separators prepared in Examples 1 to 11 and Comparative Examples 1 to 5 are used to prepare a battery cell, wherein the preparation method of the positive electrode sheet comprises: using LiNi 0.8 Co 0.1 Mn 0.1 O 2 The material is used as the positive electrode material. The positive electrode material, conductive carbon black, multi-walled carbon nanotubes and binder PVDF are mixed in a mass ratio of 97.5%:1.0%:0.5%:1.0%, and an appropriate amount of NMP is added to adjust the viscosity of the slurry to 3000-10000 Pa·S and the solid content of the slurry to 50-60% to prepare the positive electrode slurry. The prepared positive electrode slurry is coated on the positive electrode current collector aluminum foil, dried, and cold pressed to obtain the positive electrode sheet; the preparation method of the battery cell includes: stacking the positive electrode, the isolation film, and the negative electrode in order, so that the isolation film is located between the positive electrode and the negative electrode to play an isolation role. The stacking obtains a bare battery cell. The bare battery cell is placed in an outer package, injected with an electrolyte, and packaged. After the process of formation, degassing, trimming, etc., a lithium-ion battery is obtained.
[0107] The prepared battery cells were subjected to performance tests, and the test results are shown in Table 1.
[0108] (1) Energy density test:
[0109] The energy density of the lithium-ion battery was measured by charging and discharging it at a constant current of 1C / 1C in the voltage range of 2.8V-4.25V.
[0110] (2) 3C charging rate test:
[0111] At 25°C, discharge at 0.2C to 2.8V, let stand for 5 minutes, charge at 3C to 4.25V, charge at constant voltage to 0.05C and let stand for 5 minutes, the ratio of constant current charging capacity to total capacity is the charging rate.
[0112] (3) Lithium deposition and film stripping test:
[0113] After the lithium-ion battery is charged at 3C within the voltage range of 2.8V-4.25V, the electrode pieces are disassembled to observe the lithium deposition and film removal of the negative electrode piece.
[0114] (4) High temperature cycle performance test:
[0115] The test temperature is 45℃, charge to 4.25V at 1C constant current, charge to 0.025C at constant voltage, and discharge to 2.8V at 1C after standing for 5 minutes. Take the capacity obtained in this step as the initial capacity, perform 1C charge / 1C discharge cycle test, and compare the capacity of each step with the initial capacity to obtain the capacity decay curve. Record the capacity retention rate when cycling 500 times at 45℃ to compare the high temperature cycle performance of the battery.
[0116] (5) Electrode assembly full charge expansion rate test:
[0117] The thickness of the fresh electrode assembly at half charge is tested with a spiral micrometer. When the cycle reaches 500cls, the electrode assembly is in a fully charged state. The thickness of the electrode assembly at this time is tested with a spiral micrometer again. By comparing it with the thickness of the fresh electrode assembly at the initial half charge, the expansion rate of the fully charged electrode assembly at this time can be obtained.
[0118] Table 1
[0119]
[0120] It can be seen from the data in Table 1 that the battery cell prepared by applying the negative electrode sheet of the embodiment has significantly improved energy density, kinetic performance and cycle performance.
[0121] Specifically, the comparison between Examples 1 to 3 and Comparative Examples 1 and 2 shows that when the sphericity S of the second silicon material is 2 When <0.30, the surface active sites of the silicon material are significantly increased, the porosity of the upper layer increases after the pole piece is rolled, and the fast charging performance is improved. However, too many active sites cause the side reaction between the silicon material and the electrolyte to intensify, resulting in deterioration of the cycle performance and battery cell expansion. In addition, the reduction in sphericity leads to a decrease in the compaction density of the silicon material, and the pole piece cannot be pressed to the target compaction density, resulting in a decrease in the energy density of the battery cell. When the sphericity S of the second silicon material is 2When it is greater than 0.65, the surface active sites of the silicon material are reduced, the porosity of the upper layer is reduced after the electrode is rolled, and the fast charging performance is deteriorated, resulting in slight lithium deposition during 3C charging. The reduction in active sites reduces the side reactions between the silicon material and the electrolyte, and the cycle performance and battery cell expansion are improved.
[0122] The comparison between Examples 1, 4, 5, 11 and Comparative Example 3 shows that the percentage M of the first silicon material in the first negative electrode active material layer is 1 and the second silicon material percentage M in the second negative electrode active material layer 2 The gradient difference M 1 -M 2 If controlled within a reasonable range, the obtained silicon negative electrode sheet and the battery cell containing the negative electrode sheet have relatively balanced energy density, fast charging performance, cycle performance and expansion performance.
[0123] Comparison of Examples 1, 6, 7, 12 and 13 shows that the mass ratio of the first active layer and the mass ratio of the second active layer are reasonably designed, and the obtained silicon negative electrode plate and the battery cell containing the negative electrode plate have relatively balanced energy density, fast charging performance, cycle performance and expansion performance. When the mass ratio of the first active layer is less than 30%, the high-compacted lower layer active material provided is reduced, and the plate cannot be rolled to the target compaction density, the thickness of the plate increases, the energy density of the battery cell decreases, and the fast charging performance deteriorates. Moreover, at this time, the proportion of the second silicon negative electrode material of the entire plate increases, resulting in an increase in side reactions with the electrolyte, and the cycle performance and battery cell expansion deteriorate; when the mass ratio of the first active layer is greater than 70%, at this time, the overall silicon content of the plate increases, the energy density of the battery cell increases, but at this time, the proportion of the second silicon negative electrode material of the entire plate decreases, the fast charging performance deteriorates, and a slight lithium precipitation phenomenon occurs, because the proportion of the first silicon negative electrode material of the entire plate increases, which improves the cycle performance and expansion performance of the battery cell.
[0124] Comparison between Examples 1, 8, 9, 14 and 15 shows that as the mass ratio of the first silicon material of the first active layer M 1 The mass ratio M of the second silicon material of the second active layer 2 The ratio of silicon content increases, and the energy density of the battery cell increases, but the overall cycle performance and expansion performance of the battery cell deteriorate due to the increase in silicon content. Therefore, it is necessary to reasonably design the first silicon material mass ratio and the second silicon material mass ratio according to the actual battery cell design goals.
[0125] The comparison between Examples 1 and 10 and Comparative Example 4 shows that the first silicon sphericity S of the first active layer 1 The fast charging performance of the battery cell is slightly affected, but the overall structural stability of the negative electrode sheet is improved due to the improved structural stability of the silicon material, and the cycle performance and expansion performance of the battery cell are improved.
[0126] In comparative example 5, the first silicon material and the second silicon material are not coated in upper and lower layers, but are directly mixed with graphite and then coated in a single layer. Comparison between Example 1 and comparative example 5 shows that by designing the upper and lower layers of the first silicon material and the second silicon material in a gradient manner, the energy density, fast charging performance, cycle performance and expansion performance of the battery cell are significantly improved.
[0127] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A negative electrode plate, characterized in that: The negative electrode sheet comprises a current collector, a first negative electrode active material layer disposed on a surface of the current collector, and a second negative electrode active material layer disposed on a surface of the first negative electrode active material layer away from the current collector; The first negative electrode active material layer includes a first silicon material, and the second negative electrode active material layer includes a second silicon material; Wherein, the sphericity S1 of the first silicon material is ≥ 0.80; the sphericity S2 of the second silicon material is in the range of 0.30 to 0.65; The first silicon material and the second silicon material satisfy the following relationship: M1≥M2, wherein M1 represents the mass percentage of the first silicon material in the first negative electrode active material layer, and M2 represents the mass percentage of the second silicon material in the second negative electrode active material layer.
2. The negative electrode sheet according to claim 1, characterized in that: The sphericity S1 of the first silicon material is in the range of 0.80 to 0.95; the sphericity S2 of the second silicon material is in the range of 0.40 to 0.
60.
3. The negative electrode sheet according to claim 1, characterized in that: The first silicon material and the second silicon material satisfy the following relationship: 1%≤M1-M2≤5%.
4. The negative electrode sheet according to claim 1, characterized in that: The mass percentage M1 of the first silicon material in the first negative electrode active material layer is in the range of 5%≤M1≤30%; And / or, the mass percentage M2 of the second silicon material in the second negative electrode active material layer is in the range of 0<M2≤25%.
5. The negative electrode sheet according to claim 1, characterized in that: The mass ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:0.42-2.
34.
6. The negative electrode sheet according to claim 1, characterized in that: The first silicon material and the second silicon material are each independently selected from SiO x (0<x<2), at least one of pre-lithiation silicon-oxygen, pre-magnesiation silicon-oxygen, silicon alloy, sand-milled silicon-carbon and vapor-deposited silicon-carbon; The 5T powder compaction density of the first silicon material is 1.11-1.25 g / cc; The 5T powder compaction density of the second silicon material is 1.00-1.10 g / cc.
7. The negative electrode sheet according to claim 1, characterized in that: The first negative electrode active material layer further includes a first active material, and the second negative electrode active material layer further includes a second active material; Optionally, the first active material is a first graphite material, and the second active material is a second graphite material; Optionally, the first graphite material and the second graphite material are each independently selected from at least one of artificial graphite, natural graphite and mesophase carbon microbeads.
8. A method for preparing a negative electrode sheet according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: S1, preparing a first negative electrode active material layer slurry containing a first silicon material; applying the first negative electrode active material layer slurry to the surface of a current collector and performing a first drying treatment to obtain a current collector having a first negative electrode active material layer disposed on the surface; S2. Prepare a second negative electrode active material layer slurry containing a second silicon material, apply the second negative electrode active material layer slurry on the surface of the first negative electrode active material layer, and perform a second drying process.
9. The preparation method according to claim 8, characterized in that: The first negative electrode active material layer slurry further contains a first active material, a first conductive agent, a first binder, a first thickener and a first negative electrode solvent; the second negative electrode active material layer slurry further contains a second active material, a second conductive agent, a second binder, a second thickener and a second negative electrode solvent; The first conductive agent and the second conductive agent are each independently selected from at least one of conductive carbon black, graphene and carbon nanotubes; The first binder and the second binder are each independently selected from at least one of styrene-butadiene rubber, polyacrylic acid, polyvinyl pyrrolidone, polyaniline, polyimide, polysiloxane, polystyrene-butadiene rubber, epoxy resin, polyester resin and polyurethane resin; The first thickener and the second thickener are each independently selected from sodium carboxymethyl cellulose and / or lithium carboxymethyl cellulose; The first negative electrode solvent is water; The second negative electrode solvent is water.
10. A battery, characterized in that: The battery comprises a negative electrode plate, and the negative electrode plate comprises the negative electrode plate according to any one of claims 1 to 7 and / or the negative electrode plate prepared by the preparation method according to claim 8 or 9.
Citation Information
Patent Citations
Negative plate and secondary battery
CN111640913A
Negative electrode and lithium ion secondary battery thereof
CN111668452A
Negative plate and lithium ion battery
CN113745453A
Secondary battery and electric device comprising same
CN116670846A
Lithium ion secondary battery, assembly for preparing lithium ion secondary battery, preparation method and electric device
CN119069644A
Cited By
Negative pole piece, preparation method thereof and solid-state battery
CN121035131A